Analisa Pengalihan Piutang (Cessie) Berdasarkan Putusan Pengadilan Tinggi Pekanbaru Nomor: 13/PDT/2017/PT.PBR Junto Putusan Pengadilan Negeri Bangkinang Nomor: 6/PDT.G/2016/PN.BKN - Suhardi, Suhardi; Ismi, Hayatul; Firmanda S, Hengki (CV. Rayyan Dwi Bharata, 2025)
Banking is something related to banks, including institutions, business activities, and methods or processes in implementing business activities. One of the activities of financial institutions is banking that has credit facilities. In practice, Cessie often causes problems between the parties. Many Cessie cases occur especially between customers and the Bank. This type of legal research is categorized as a type of normative legal research. Normative legal research is library legal research. The data sources used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques come from the literature study method. After the data is collected, conclusions are drawn. This normative research data is analyzed qualitatively. From the research results, 2 (two) main points were obtained, namely first, the transfer of receivables through cession does not result in the termination of the credit agreement made between the creditor and the debtor, it only results in the transfer of the right to collect or receivables from the debtor (cessus) to a third party who then replaces the position of the old creditor (cedent) as the new creditor (cessionaris). Second, the transfer (cession) carried out by the old creditor (cedent) to the new creditor (cessionaris) is an act that is justified by law, but the actions taken by the new creditor (cessionaris) against the debtor are unlawful acts. The researcher's suggestion is first, to provide detailed provisions on the transfer of receivables through cession in the form of a Ministerial Decree or other Regulations in the Legislation. Second, for all new creditors (cessionaris) in the future before taking legal action, it is expected to take preventive steps for creditors to find the best ways to resolve bad debts so that the parties get their rights and do not harm each other.